Performance of organic grain legumes in Tuscany - Valentina Moschini; Giovanna Casella; Roberto Vivoli; Concetta Vazzana; Andrea Martini; Claudia Lotti; Paola Migliorini (Italian Journal of Agronomy, 2014)
In 2005-2007 growing season, few varieties of field bean, high protein pea and white lupin were compared in an organic farm of Central Italy (Mugello area, Tuscany), to evaluate their agronomic performance in terms of grain yield, nutritional quality and competitive ability against weeds. The experiment was performed under rain-fed conditions. Furthermore, grain legumes features were compared between two different sowing seasons (autumnal vs late-winter) for two years, in order to get information on the best time of sowing of these species, and the stability of yields of different genotypes in those climatic and soil conditions. These legumes could be an alternative protein source to external soybean, a high-risk alimentary source of genetically modified organisms, in the organic livestock sector. The main findings indicate that higher yields in grain and crude protein were obtained with the pea species and in particular with cultivars Hardy (4.0 t/ha grain yield; 626 kg/ha crude protein yield) and Classic (3.1 t/ha grain yield; 557 kg/ha crude protein yield); followed by field bean cv. Chiaro di Torre Lama (2.9 t/ha grain yield; 624 kg/ha crude protein yield) and cv. Vesuvio (2.5 t/ha grain yield; 549 kg/ha crude protein yield). Furthermore the field bean is interesting for the stability of yield in both years despite climatic conditions rather different. The white lupin has showed the lower yield but the best values of grain quality, with higher values in lupin Multitalia for dry matter, crude protein and ether extract and in lupin Luxe also for crude fibre, respect to the other legumes analysed. Among lupin varieties, lupin Multitalia showed the best yield results for the pedo-climatic conditions of Mugello area (0.9 t/ha lupin Multitalia; 0.2 t/ha lupin Luxe). The total yield of organic grain legumes, in the experimental site, is resulted higher with an autumnal seeding respect to the late-winter seeding (2.8 t/ha vs 1.9 t/ha).